PELATIHAN DAN PENDAMPINGAN MANAJEMEN KINERJA BAGI PENGELOLA BADAN USAHA MILIK DESA (BUMDES) DALAM PENGEMBANGAN EKONOMI LOKAL DI DESA CIKAMUNDING KECAMATAN CILOGRANG, KABUPATEN LEBAK - Sapari Sapari; Rhifwan Aji Bimantoro Ardiyanto; Baedilah Baedilah; Ghaisani Ramadhani Putri; Noviyanti Mulyana (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
This Community Service (PkM) activity aims to enhance the capacity and professionalism of BUMDes governance in Cikamunding Village, Cilograng District, Lebak Regency. This performance management training and mentorship program was initiated to address partner constraints, such as a low understanding of business planning, weak financial administration, and underutilized local economic potential. Through strengthening performance management, BUMDes is expected to transform into a productive, adaptive, and sustainable driver of the village economy. The implementation method was designed systematically, participative, educatively, and interactively. The stages began with a situational analysis and needs identification, followed by delivering conceptual materials on performance management, work targets, and business development strategies. The results demonstrated a significant increase in the knowledge, insights, and managerial skills of BUMDes managers, where the average overall score escalated from 44.6% to 84.6%.